Familial occurrence of nodular regenerative hyperplasia of the liver: a report on three families. (1st August 1999) - Dumortier, J; Boillot, O; Chevallier, M; Berger, F; Potier, P; Valette, P-J; Paliard, P; Scoazec, J-Y
Abstract : BACKGROUND/AIMS: Nodular regenerative hyperplasia of the liver is a histological lesion usually associated with systemic diseases, haematological malignancies, or drugs. Its prognosis depends on portal hypertension, which usually is well tolerated and requires medical management only. PATIENTS: Three unrelated families, in which two sibling adult male patients presented with nodular regenerative hyperplasia of the liver, were studied. METHODS: Complete clinical charts and liver biopsy specimens were available for all patients. In addition, explanted livers were available for examination for the two transplanted patients. RESULTS: There was no evidence of any of the various clinical situations known to be associated with nodular regenerative hyperplasia of the liver. Portal hypertension was severe, requiring surgical treatment in two cases. Renal lesions were present in three patients. In two patients, progressive evolution to liver atrophy and hepatic failure, associated with renal failure, led to combined liver and renal transplantation. CONCLUSIONS: This report describes the existence of familial cases of nodular regenerative hyperplasia of the liver, occurring without underlying or associated systemic disease, characterised by a poor clinical course and often associated with progressive renal failure.